Charismatic Species as Indicators of Plastic Pollution in the Río de la Plata Estuarine Area, SW Atlantic - González Carman, Victoria; Denuncio, Pablo; Vassallo, Martina; Berón, María Paula; Álvarez, Karina C.; Rodriguez-Heredia, Sergio (Frontiers in Marine Science, 2021)
Marine plastic pollution is projected to increase globally in the next few decades. This holds true for South America where the number of species that interacts with plastics is increasing. In this study, we explore for the first time the potential of certain charismatic species of marine turtles, mammals and seabirds as indicators of plastic pollution in the Río de la Plata (RdP), one of the largest and most important estuarine areas of the Southwest Atlantic. Through a revision of published studies integrated with unpublished data, we summarize studies on the interaction of charismatic marine species with plastics in the region and evaluate their role as indicators of plastic pollution in the RdP based on aspects of their local ecology and key attributes (i.e., biological/ecological, methodological, and conservation attributes) of indicator species. We found that at least 45 charismatic marine species interact –whether by ingestion or entanglement– with plastics in the region. Eight of these species were selected as potential indicators given their occurrence, probability of sampling and interaction with plastics in the RdP, namely: Chelonia mydas, Caretta caretta, Dermochelys coriacea, Pontoporia blainvillei, Arctocephalus australis, Otaria flavescens, Larus dominicanus, and Spheniscus magellanicus. The species shared some key attributes of indicator species, e.g., they are relatively well studied, but differed in critical aspects such as their home range and mobility. We discuss whether the species’ attributes are strengths or weaknesses according to the available knowledge on their ecology in the RdP, and propose a multispecies indicator of plastic pollution given that those strengths and weaknesses can be compensated among species. Monitoring plastic pollution through a combination of species would enable a better understanding of plastic pollution in this relevant area.